PKM Pendampingan Penyusunan Pembelajaran Proyek Penguatan Profil Pelajar Pancasila dengan CBL (Challenge Base Learning) - Riska, Muhammad; Ruslan; Muchtar, Akhyar (Jurusan Teknik Informatika dan Komputer, 2023)
The Community Partnership Program (PKM) partner is Cluster 3 Bangkala, Jeneponto Regency. The problem is divided into 2, namely the knowledge aspect and the practical aspect. The knowledge aspect is: Elementary school teachers in Cluster 3 Bangkala Jeneponto Regency do not yet know the steps for learning the CBL Base Proyek Penguatan Profil Pelajar Pancasila (P5). The practical aspect of the service partner, namely the teacher at SD Gugus 3 Bangkala, Jeneponto Regency, does not have experience implementing Penguatan Profil Pelajar Pancasila (P5). The model applied in training with the methods used are: lectures, demonstrations, discussions, questions and answers, collaboration and assignments. Which was carried out at one of the Bangkala cluster 3 schools, Kab. Jeneponto which was attended by 60 teachers from 8 schools that are members of cluster 3 Bangkala Regency. Jeneponto. The results achieved are from the knowledge aspect that the partner teacher knows the steps for learning the CBL-based Penguatan Profil Pelajar Pancasila (P5) and practically the partner teacher is able to design learning for the CBL-based Penguatan Profil Pelajar Pancasila (P5) in learning activities.